Darkest hour - Brooke, Lauren (New York, NY : Scholastic, 2003)
An equine flu is infecting Heartland's horses despite Amy and Ty's best efforts to control the spread of the infectious sickness.
"Healing horses, healing hearts ..."--Cover.
G4
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Children's stories